Near-equilibrium chemical vapor deposition of high-quality single-crystal graphene directly on various dielectric substrates - Chen, Jianyi (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.